2021
DOI: 10.1093/g3journal/jkab031
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assembly of the Canadian two-row Malting Barley cultivar AAC Synergy

Abstract: Barley (Hordeum vulgare L.) is one of the most important global crops. The six-row barley cultivar Morex reference genome has been used by the barley research community worldwide. However, this reference genome can have limitations when used for genomic and genetic diversity analysis studies, gene discovery, and marker development when working in two-row germplasm that is more common to Canadian barley. Here we assembled, for the first time, the genome sequence of a Canadian two-row malting barley, cultivar AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The complete Hvu-Abermu elements in barley was compared and found that they can share more than 95% sequence identity suggesting that Hvu-Abermu may be an active mutator. To detect its transpositional activity, the 600-bp flanking sequences (300-bp for each side) of the 284 Hvu_Abermu transposons with well-defined boundaries in the reference barley genome from the malting barley cultivar “Morex” ( Mascher et al, 2017 ) were used to search against the genomes of 22 cultivated and wild barley accessions, including 18 cultivated barley genotypes and one accession of wild barley (B1K-04-12) generated by the barley pan-genome project ( Jayakodi et al, 2020 ; Schreiber et al, 2020 ), one Canadian malting barley cultivar “AAC Synergy” ( Xu et al, 2021 ), one Tibetan hulless barley “Lasa Goumang” ( Zeng et al, 2020 ) and another wild barley accession AWCS276 (WB1; Liu et al, 2020 ). No hits or multiple highly identical hits were detected for the flanking sequences of 160 Hvu_Abermu transposons suggesting that these Hvu_Abermu elements were either inserted into highly repetitive regions or the flanking regions were not sequenced and/or assembled in the 22 genomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The complete Hvu-Abermu elements in barley was compared and found that they can share more than 95% sequence identity suggesting that Hvu-Abermu may be an active mutator. To detect its transpositional activity, the 600-bp flanking sequences (300-bp for each side) of the 284 Hvu_Abermu transposons with well-defined boundaries in the reference barley genome from the malting barley cultivar “Morex” ( Mascher et al, 2017 ) were used to search against the genomes of 22 cultivated and wild barley accessions, including 18 cultivated barley genotypes and one accession of wild barley (B1K-04-12) generated by the barley pan-genome project ( Jayakodi et al, 2020 ; Schreiber et al, 2020 ), one Canadian malting barley cultivar “AAC Synergy” ( Xu et al, 2021 ), one Tibetan hulless barley “Lasa Goumang” ( Zeng et al, 2020 ) and another wild barley accession AWCS276 (WB1; Liu et al, 2020 ). No hits or multiple highly identical hits were detected for the flanking sequences of 160 Hvu_Abermu transposons suggesting that these Hvu_Abermu elements were either inserted into highly repetitive regions or the flanking regions were not sequenced and/or assembled in the 22 genomes.…”
Section: Resultsmentioning
confidence: 99%
“…To validate the computational analyses performed, 16 barley genotypes were collected for PCR analysis including “Morex,” “Golden Promise” and other five cultivated barley varieties that genomes have been sequenced by the barley pan-genome and other projects ( Jayakodi et al, 2020 ; Schreiber et al, 2020 ; Xu et al, 2021 ). We were not able to obtain the seeds or DNAs for “Lasa Goumang” and two wild barley B1K-04-12 and AWCS276 (WB1) but we collected four Tibetan hulless varieties and five wild barley accessions from the National Small Grains Collection (NSGC) at the USDA ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations